Epidural blood patch for post-dural puncture headaches in adult and paediatric patients with malignancies: a review. (June 2021) - Morgan, Kyle J.; Mohan, Rahul; Karol, Seth E.; Flerlage, Jamie
Summary: Many anaesthetists are hesitant to perform epidural blood patch in patients with cancer because of the potential risk of seeding the CNS with malignant cells. Recent evidence suggests that anaesthetists may view malignancy as a relative contraindication to epidural blood patch rather than an absolute contraindication. This review article summarises the clinical dilemma, reviews the existing literature, and proposes a treatment algorithm that includes the utilisation of for the management of post-dural puncture headache in the oncology population.